Assessment of Likelihood Ratio for Four Contact Dermatitis Symptoms of Vinca Minor - Bagchi, Suman; Nayak, Chaturbhuja; Rutten, Lex; Koley, Munmun; Saha, Subhranil; Roy, Mousumi; Abbas, Sk Jahir; Ghosh, Simantini; Halder, Suman; Wani, Ghulam Nabi; Mir, Anaitulah Ahmad; Bhat, Showket Ahmad (Homeopathy, 2018)
Background Contact dermatitis (CD) is a frequently occurring medical condition, for which Vinca minor (VM) is one of the recommended homeopathic medicines. However, the symptoms indicating this medicine have not yet been assessed systematically. Likelihood ratio (LR), based on Bayesian statistics, may yield better estimation of a medicine's indication than the existing method of entry of symptoms into materia medica and repertories.Methods We investigated LRs of four CD symptoms of VM: (1) great sensitiveness of skin, with redness and soreness from slightest rubbing; (2) weeping eczema with foul, thick crusts; (3) itching amelioration in open air; and (4) CD of scalp. An observational, prospective, patient-outcome study was conducted in five different practice settings on 390 CD patients over 18 months using three outcomes—Glasgow Homeopathic Hospital Outcome Scale (GHHOS), Scoring Atopic Dermatitis (SCORAD), and Dermatology Life Quality Index (DLQI), assessed at baseline, after 3 and 6 months. The LR of each of the four symptoms was estimated as per the patient-rated outcomes on GHHOS.Results Seventy-four VM and 316 non-VM cases were analyzed. Estimated LRs were as follows: symptom 1, 1.29 (95% confidence interval [CI]: 0.65 to 2.60); symptom 2, 1.48 (95% CI: 0.80 to 2.74); symptom 3, 1.70 (95% CI: 0.94 to 3.07); symptom 4, 1.36 (95% CI: 0.74 to 2.51). There were statistically significant reductions in SCORAD and DLQI scores over 3 and 6 months.Conclusion There was insufficient evidence to attribute any of the four assessed symptoms clearly to VM. Though non-significant, a high LR was observed for “itching amelioration in open air” (symptom 3). Symptoms in the homeopathic materia medica for VM are perhaps over-represented. More research of this nature is warranted.
Keywords: homeopathy; Vinca minor; contact dermatitis; likelihood ratio